2017
DOI: 10.1016/j.ejmech.2016.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of new hit-molecules targeting Plasmodium falciparum through a global SAR study of the 4-substituted-2-trichloromethylquinazoline antiplasmodial scaffold

Abstract: From 4 antiplasmodial hit-molecules identified in 2-trichloromethylquinazoline series, we conducted a global Structure-Activity relationship (SAR) study involving 26 compounds and covering 5 molecular regions (I - V), aiming at defining the corresponding pharmacophore and identifying new bioactive derivatives. Thus, after studying the aniline moiety in detail, thienopyrimidine, quinoline and quinoxaline bio-isosters were synthesized and tested on the K1 multi-resistant P. falciparum strain, along with a cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 48 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…16 Some more recent modulations of the position 4 of this pharmacophore failed to achieve more active derivatives. 17,18 Here, we present a comprehensive study of the structure-activity relationships of this pharmacophore, especially focusing on the modulation of the redox potentials. Thirty one pharmacophore derivatives, substituted at positions 3, 4, 5, 6 and 7, were synthesized and their in vitro cytotoxicity and activities against L. infantum (axenic amastigotes), and T. brucei brucei (trypomastigotes) were first determined.…”
Section: Introductionmentioning
confidence: 99%
“…16 Some more recent modulations of the position 4 of this pharmacophore failed to achieve more active derivatives. 17,18 Here, we present a comprehensive study of the structure-activity relationships of this pharmacophore, especially focusing on the modulation of the redox potentials. Thirty one pharmacophore derivatives, substituted at positions 3, 4, 5, 6 and 7, were synthesized and their in vitro cytotoxicity and activities against L. infantum (axenic amastigotes), and T. brucei brucei (trypomastigotes) were first determined.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthily, previous research in our laboratory led to the discovery of a series of novel indole analogs possessing excellent antimicrobial, antioxidant, and anticancer activities . Most interestingly, more recent literature survey has revealed that the incorporation of a thiophene moiety can significantly enhance the antimicrobial activity of candidate compounds …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that the CCl 3 group is mandatory to provide antiplasmodial activity [ 28 , 29 , 30 ]. To confirm the key role played by the 3-CCl 3 group of the most potent compound ( 3i ) in phenoxyquinoxaline series, the CCl 3 group was replaced by a proton ( 3u ), a CH 3 group ( 2i ), a CF 3 group ( 3v ), and a CHCl 2 group ( 3w ).…”
Section: Resultsmentioning
confidence: 99%